PERANAN GURU PENDIDIKAN AGAMA KRISTEN (PAK) DALAM PENGINJILAN - Megawati Manullang (Jurnal Christian Humaniora, 2019)
Social media often notifies that some teacher did praiseworthy deeds, especially actions that harmed students. Those behaviors were including rape, beatings, extortion in the field of material, and many other cases. Actually, a teacher is expected to be a role model by their words and behavior blessing students. Especially, the profession as a Christian religious education teacher is not same as other teachers. Christian religious education teachers have more difficult duties and responsibilities which not only providing information and knowledge to students, but they also bring students to experience a special meeting with Christ and have a new life in Christ. Therefore, to meet this main responsiblities, Christian religious education teacher must carry out evangelism.BAHASA INDONESIA ABSTRACT: Media sosial sering memberitakan tentang perbuatan dari beberapa guru yang tidak terpuji, khususnya perbuatan yang merugikan para muridnya sendiri. Baik itu tindakan pemerkosaan, pemukulan, pemerasan dalam bidang materi, dan masih banyak lagi kasus yang lain. Padahal seorang guru diharapkan menjadi teladan, baik dalam perkataan, tingkahlaku yang menjadi berkat bagi siswa. Terutama profesi sebagai guru Pendidikan Agama Kristen (PAK) tidak sama dengan guru-guru umum lainnya, guru PAK memiliki tugas dan tanggung jawab yang lebih berat, bukan hanya sekedar memberikan informasi dan ilmu pengetahuan kepada peserta didik tetapi yang paling utama adalah membawa peserta didik mengalami perjumpaan dengan Kristus dan memiliki hidup baru di dalam Kristus. Maka untuk mencapai hal tersebut guru PAK wajib melaksanakan penginjilan.Keywords: Christian religious education teacher; evangelism; students